2016
DOI: 10.3390/technologies4040037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Microstructure and Mechanical Properties of Al-Based Composite Reinforced with 10 Vol.% Mechanically Alloyed Mg-7.4%Al Particles

Abstract: Abstract:The effect of Mg-7.4%Al reinforcement particle size on the microstructure and mechanical properties in pure Al matrix composites was investigated. The samples were prepared by hot consolidation using 10 vol.% reinforcement in different size ranges, D, 0 < D < 20 µm (0-20 µm), 20 ≤ D < 40 µm (20-40 µm), 40 ≤ D < 80 µm (40-80 µm) and 80 ≤ D < 100 µm (80-100 µm). The result reveals that particle size has a strong influence on the yield strength, ultimate tensile strength and percentage elongation. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…The effect of reinforcing Al matrix with a different particles size of 10 AlMg was investigated and the results showed that decreasing the particles size of 10 AlMg leads to increase the density of the composite material. 20 Hafed Ibrahim et al. studied the effect of cobalt activator addition on the density of W-25Cu composites.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of reinforcing Al matrix with a different particles size of 10 AlMg was investigated and the results showed that decreasing the particles size of 10 AlMg leads to increase the density of the composite material. 20 Hafed Ibrahim et al. studied the effect of cobalt activator addition on the density of W-25Cu composites.…”
Section: Resultsmentioning
confidence: 99%
“…Chaubey et al [29] examined the impact of Mg filler of 7.4% grain size on produced AMCs. There were four variations of Mg particle sizes: 0-20 µm, 20-40 µm, 40-80 µm, and 80-100 µm.…”
Section: Introductionmentioning
confidence: 99%
“…The settlement of particles at the borders results in formation of cracks and reduced mechanical properties of samples. 24 a a a Furthermore, the images show that nanocomposite samples have lower porosity compared to microcomposite samples having the same volume fraction. A lower porosity indicates a stronger bond between particles.…”
Section: Microstructural Examinationsmentioning
confidence: 98%